Brachiaria species influence nitrate transport in soil by modifying soil structure with their root system - Galdos, M.; Brown, E.; Rosolem, C. A. [UNESP]; Pires, L. F.; Hallett, P. D.; Mooney, S. J. (Nature Publishing Group, 2020)
Leaching of nitrate from fertilisers diminishes nitrogen use efficiency (the portion of nitrogen used by a plant) and is a major source of agricultural pollution. To improve nitrogen capture, grasses such as brachiaria are increasingly used, especially in South America and Africa, as a cover crop, either via intercropping or in rotation. However, the complex interactions between soil structure, nitrogen and the root systems of maize and different species of forage grasses remain poorly understood. This study explored how soil structure modification by the roots of maize (Zea maize), palisade grass (Brachiaria brizantha cv. Marandu) and ruzigrass (Brachiaria ruziziensis) affected nitrate leaching and retention, measured via chemical breakthrough curves. All plants were found to increase the rate of nitrate transport suggesting root systems increase the tendency for preferential flow. The greater density of fine roots produced by palisade grass, subtly decreased nitrate leaching potential through increased complexity of the soil pore network assessed with X-ray Computed Tomography. A dominance of larger roots in ruzigrass and maize increased nitrate loss through enhanced solute flow bypassing the soil matrix. These results suggest palisade grass could be a more efficient nitrate catch crop than ruzigrass (the most extensively used currently in countries such as Brazil) due to retardation in solute flow associated with the fine root system and the complex pore network.